1999
DOI: 10.1038/sj.gt.3300887
|View full text |Cite
|
Sign up to set email alerts
|

Allele replacement: an application that permits rapid manipulation of herpes simplex virus type 1 genomes

Abstract: Herpes simplex virus (HSV) is a new platform for gene therapy. We cloned the human herpesvirus HSV-1 strain F genome into a bacterial artificial chromosome (BAC) and adapted chromosomal gene replacement technology to manipulate the viral genome. This technology exploits the power of bacterial genetics and permits generation of recombinant viruses in as few as 7 days. We utilized this technology to delete the viral packaging/cleavage (pac) sites from HSV-BAC. HSV-BAC DNA is stable in bacteria and the pac-delete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
73
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(73 citation statements)
references
References 29 publications
0
73
0
Order By: Relevance
“…Previously, we and Rapid method to generate oncolytic HSV vectors K Terada et al others reported the cloning of the entire HSV-1 genome as a BAC, which allowed for stable maintenance as well as versatile genetic modifications of the highly repetitive HSV genomic sequences in bacteria and spontaneous rescue of recombinant viruses upon transfection of the HSV-BAC DNA into mammalian cells. 15,[18][19][20][21] In order to facilitate the process of engineering oncolytic HSV vectors, particularly for introducing various therapeutic transgenes into a defined oncolytic HSV vector backbone (e.g., U L 39-and g 1 34.5-double mutant), we devised a novel BAC-based methodology called the HSVQuik system. This system consists of two components, an HSV-BAC carrying the entire MGH1 9 genome (fHsvQuik-1) and a replication-conditional shuttle plasmid (pTransfer) (Figure 2b).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we and Rapid method to generate oncolytic HSV vectors K Terada et al others reported the cloning of the entire HSV-1 genome as a BAC, which allowed for stable maintenance as well as versatile genetic modifications of the highly repetitive HSV genomic sequences in bacteria and spontaneous rescue of recombinant viruses upon transfection of the HSV-BAC DNA into mammalian cells. 15,[18][19][20][21] In order to facilitate the process of engineering oncolytic HSV vectors, particularly for introducing various therapeutic transgenes into a defined oncolytic HSV vector backbone (e.g., U L 39-and g 1 34.5-double mutant), we devised a novel BAC-based methodology called the HSVQuik system. This system consists of two components, an HSV-BAC carrying the entire MGH1 9 genome (fHsvQuik-1) and a replication-conditional shuttle plasmid (pTransfer) (Figure 2b).…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial artificial chromosome (BAC) is a single-copy plasmid that can stably retain a large size (f300 kb) DNA as an insert (12). BAC plasmids have been used to propagate the entire HSV-1 genome in Escherichia coli, allowing an easy genetic manipulation (13,14). In this article, we use a new BAC-using method for generating ''armed'' oncolytic HSV-1 vectors with the backbone of MGH-1, an oncolytic HSV-1 vector with the genome structure identical to G207 (i.e., deletions in both copies of the c34.5 gene and a lacZ insertion inactivating the ICP6 gene; ref.…”
mentioning
confidence: 99%
“…Recently, the large DNA genomes of a baculovirus (12) and several herpesviruses (13)(14)(15)(16)(17)(18) have been cloned as bacterial artificial chromosomes (BACs). These circular miniF BAC plasmids allow viral genomes to be stably maintained at low copy number and manipulated in Escherichia coli and then reconstituted as infectious virus by transfection of eukaryotic cells.…”
mentioning
confidence: 99%